2022
DOI: 10.1080/14756366.2022.2062336
|View full text |Cite
|
Sign up to set email alerts
|

Bat coronaviruses related to SARS-CoV-2: what about their 3CL proteases (MPro)?

Abstract: Despite a huge effort by the scientific community to determine the animal reservoir of SARS-CoV-2, which led to the identification of several SARS-CoV-2-related viruses both in bats and in pangolins, the origin of SARS-CoV-2 is still not clear. Recently, Temmam et al. reported the discovery of bat coronaviruses with a high degree of genome similarity with SARS-CoV-2, especially concerning the RBDs of the S protein, which mediates the capability of such viruses to enter and therefore infect human cells through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The congruence between our structural prediction and the experimental data supports the idea that the overall fold of the main protease is conserved across several variants and that the structural effect that residue mutations could have on the effectiveness of the main protease inhibitor could be accurately predicted through the combination of computational techniques such as homology modelling, molecular docking, and molecular dynamics. Moreover, based on available structural information, the high degree of structural similarity between the main proteases is not only shared by variants of the SARS-CoV-2 virus but also by other coronaviruses such as bat coronavirus 13 , the Porcine transmissible Gastroenteritis virus (TGEV) 78 , Human coronavirus strain 229E (HCoV) 80 , Infectious bronchitis virus (IBV) 88 and MERS-CoV 89 , thereby validating the pursue of novel M pro inhibitors that could act as pan-coronaviral drugs and help to prevent future coronavirus associated pandemics.…”
Section: Resultsmentioning
confidence: 99%
“…The congruence between our structural prediction and the experimental data supports the idea that the overall fold of the main protease is conserved across several variants and that the structural effect that residue mutations could have on the effectiveness of the main protease inhibitor could be accurately predicted through the combination of computational techniques such as homology modelling, molecular docking, and molecular dynamics. Moreover, based on available structural information, the high degree of structural similarity between the main proteases is not only shared by variants of the SARS-CoV-2 virus but also by other coronaviruses such as bat coronavirus 13 , the Porcine transmissible Gastroenteritis virus (TGEV) 78 , Human coronavirus strain 229E (HCoV) 80 , Infectious bronchitis virus (IBV) 88 and MERS-CoV 89 , thereby validating the pursue of novel M pro inhibitors that could act as pan-coronaviral drugs and help to prevent future coronavirus associated pandemics.…”
Section: Resultsmentioning
confidence: 99%
“…In the context of the COVID-19 pandemic, where the extraordinary effort promoted by the scientific community quickly made several experimentally determined structures available, the relevance of structural modeling was highlighted by the ability to keep up with the high mutation rate of the virus [135,207], other than providing a useful starting point for drug discovery campaigns for a target whose structure had yet to be elucidated [267,268]. For example, several studies were conducted to investigate the impact of mutations found in both the spike protein [135,[269][270][271][272][273] and the main protease [135,198,274,275] of emerging strains on viral fitness and resistance to existing therapies. These studies showed that relatively inexpensive approaches such as homology modeling and positional scanning can be reliable tools to rationalize the origin of the virus [274,[276][277][278], quickly track the evolution of the original strain [135,279,280], predict the impact of future possible mutations [270,272] and adjust existing therapeutics tools accordingly [198,281].…”
Section: Cadd Strategies Against Covid-19mentioning
confidence: 99%
“…For example, several studies were conducted to investigate the impact of mutations found in both the spike protein [135,[269][270][271][272][273] and the main protease [135,198,274,275] of emerging strains on viral fitness and resistance to existing therapies. These studies showed that relatively inexpensive approaches such as homology modeling and positional scanning can be reliable tools to rationalize the origin of the virus [274,[276][277][278], quickly track the evolution of the original strain [135,279,280], predict the impact of future possible mutations [270,272] and adjust existing therapeutics tools accordingly [198,281].…”
Section: Cadd Strategies Against Covid-19mentioning
confidence: 99%